Antifungal Activity of Ginger Rhizome Extract against Fusarium solani - Ke-Yong Xi; Shi-Jie Xiong; Gang Li; Chang-Quan Guo; Jie Zhou; Jia-Wei Ma; Jun-Liang Yin; Yi-Qing Liu; Yong-Xing Zhu (Horticulturae, 2022)
Fusarium solani is one of the most ruinous soil-borne pathogens and seriously affects crop yields and quality worldwide. Ginger is an important medicinal crop, and ginger rhizome extract (GRE) has been used as an alternative for chemical fungicides and bactericides. We investigated the fungistatic effect of GRE on F. solani and analyzed the chemical constituents of GRE using UPLC-MS/MS. Antifungal assay results showed that 20 mg/mL of GRE completely inhibited the growth of F. solani. Morphological analysis revealed that GRE destroyed the morphology and structure of mycelia, thus inhibiting mycelial growth. Furthermore, GRE suppressed the activities of cell wall-degrading and cellular respiratory-related enzymes and decreased the content of fusaric acid, which reduced or even abrogated the infection ability of F. solani. UPLC-MS/MS analysis showed that GRE constituents belonged to eight categories, among which phenolic acids were the highest in content (46.29%) and tannins were the lowest in content (0.06%). When the antifungal activities of major phenolic and flavonoid compounds were evaluated, 4.0 mg/mL 4-hydroxybenzaldehyde and 15.0 mg/mL quercetin were found to completely inhibit F. solani growth. These results highlight GRE as an excellent source of antifungal compounds and suggest the possibility of using 4-hydroxybenzaldehyde and quercetin as natural fungicides to control crop diseases.